2015
DOI: 10.1017/jfm.2015.465
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram for droplet impact on superheated surfaces

Abstract: We experimentally determine the phase diagram for impacting ethanol droplets on a smooth, sapphire surface in the parameter space of Weber number We versus surface temperature T. We observe two transitions, namely the one towards splashing (disintegration of the droplet) with increasing We, and the one towards the Leidenfrost state (no contact between the droplet and the plate due to a lasting vapour film) with increasing T. Consequently, there are four regimes: contact and no splashing (deposition regime), co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 41 publications
6
71
2
Order By: Relevance
“…Since the surface to cools down as a result of the presence of the drop, the wetted areas with their entrapped bubbles can survive on the surface, resulting in the spray formation by the bursting of the bubbles at the top surface of the drop, in agreement with previous studies on spray formation [66,97]. Furthermore, we find the boundary between contact boiling and transition boiling to be weakly dependent on the impact velocity, similarly as reported for ethanol drops impacting on glass [57] and on sapphire [45,69]. Since no cooling was found in the latter two studies, it is not surprising that no spray is formed:…”
Section: Reflection On Existing Literaturesupporting
confidence: 91%
See 3 more Smart Citations
“…Since the surface to cools down as a result of the presence of the drop, the wetted areas with their entrapped bubbles can survive on the surface, resulting in the spray formation by the bursting of the bubbles at the top surface of the drop, in agreement with previous studies on spray formation [66,97]. Furthermore, we find the boundary between contact boiling and transition boiling to be weakly dependent on the impact velocity, similarly as reported for ethanol drops impacting on glass [57] and on sapphire [45,69]. Since no cooling was found in the latter two studies, it is not surprising that no spray is formed:…”
Section: Reflection On Existing Literaturesupporting
confidence: 91%
“…Because of the absence of the spray, Staat et al [69] identified all impacts above this boundary to be film boiling, though in later studies the lower part of this regime was named and identified as the transition boiling regime [57,57].…”
Section: Conclusion 85mentioning
confidence: 99%
See 2 more Smart Citations
“…On even hotter surfaces, however, beyond the socalled Leidenfrost temperature T L , the droplet interface becomes smooth again without any bubbles inside it. In this regime the droplet lives much longer, as now it levitates on its own vapor layer: the well-known Leidenfrost effect [9,10].In order to determine the Leidenfrost temperature T L and its dependence on the impact velocity U, phase diagrams have been experimentally produced for various impacting droplets with many combinations of substrates and liquids: water on smooth silicon [8], water on microstructured silicon [11], FC-72 on carbon nanofiber [12], water on aluminium [13], and ethanol on sapphire [14]. All of these phase diagrams show a weakly increasing behavior of T L with U.…”
mentioning
confidence: 99%